Gas production, volatile fatty acids and ammonia nitrogen in vitro with diets based on dry pasture - Rodr?guez Muela, C.; Aguirre, E.; Salvador, F.; Ruiz, O.; Arzola, C.; La O, Oreste; Villalobos, C. (Cuban Journal of Agricultural Science, 2010)
The object of this study was assess the effect of the urea level (UL) on multinutrient blocks, as well as the different ratios of dry pasture, supplement in the form of multinutrient block (MB) on the gas production (GP), volatile fatty acids (acetic, propionic, and butyric) (VFA) and ammonia nitrogen (N-NH3) in vitro. The following parameters of GP were evaluated: asymptote of gas production (GP-A), mean time of gas formation after incubation (GP-B), constant indicating the change of profile (GP-C), point of inflexion (GP-t1), fractional fermentation ratio (GP-R), and time of maximum fractional fermentation ratio (GP-tRm). The multinutrient blocks were used (PREMIUM BLOCK?) with 0, 2.5, 5, and 7.5 % of urea, and diets were elaborated with ratio of 6, 12, and 18 % of block and the rest with the dry pasture from an open air middle rangeland of the northwestern region of the Chihuahua state, Mexico. For GP, there was effect (P < 0.03) of interaction between the UL and the MB since 6 h after the start of the gas production, which was kept similar until 12 h (P < 0.01), when there was a shift and, since that time, the effect was kept the same until 96 h (P < 0.01), with the lowest value for the treatment UL 0 % and MB 18 % (31.50 mL/200 mg DM), and the highest for UL 5 % and MB 6 % (34.33 mL/200 mg DM). These changes showed movements in the fermentation profiles, due to the different combination of substrates. There was effect of interaction (P < 0.01) of UL and MB in GP-B, GP-t1 and GP-tRm and recorded the same effect (P < 0.07) in GP-R. It was assumed that the MB accelerated the fermentation and the UL increased the availability of the substrates. The MB showed linear effect (P < 0.02) on GP-A and GP-C, where both variables were diminished by increasing the MB. This indicates that the fermentation was accelerated with the increase of the MB. For the production of N-NH3, the MB had positive linear effect (P < 0.01), indicating that as the MB was increased, the concentration of N-NH3 was also increased, whereas the UL had cubic effect (P < 0.13) because the highest concentration of N-NH3 occurred when the UL had values of 2.5 and 7.5 % and the lowest concentration was recorded when the UL reached values of 0 and 5 %, due maybe to a more efficient synthesis of protein. There was no effect of any kind on the VFA. It was concluded that the 5 % of the UL in the block and the 12 % of block inclusion in the diet produced the best performance of the indicators of the rumen fermentation. Further studies with animals are suggested, as well as their economic assessment. Key words: gas production, multinutrient blocks, urea, dry pasture.